The Effectiveness of AI-Assisted Interactive Learning Media to Improve Elementary School Students' Digital Literacy - Gede Riyan Permana; Komang Dani Indra Mustika; Gede Sutha Andhika Kristian Rafael; Gede Agus Darmayasa; Sang Made Widi Kesuma; Gede Vical Suyuda (Jurnal Pendidikan Guru Sekolah Dasar, 2026)
The development of digital technology and artificial intelligence (AI) has brought major changes in the world of education, including at the elementary school level. However, students' digital reading and writing skills remain a problem because the use of technology in the teaching and learning process has not been running well. This study aims to see how effective AI-supported interactive learning media is in improving the digital literacy skills of elementary school students. The method used is a Systematic Literature Review (SLR) that follows the PRISMA 2020 guidelines. Data was taken from scientific publications registered in Google Scholar between 2020 and 2025 using keywords related to interactive learning media, educational technology, AI-based learning, and innovation in learning. The results of the study from 10 articles that met the criteria showed that AI-supported interactive learning media provides good benefits in improving digital literacy, conceptual understanding, learning motivation, critical thinking skills, and also student engagement in the learning process. The integration of AI makes learning more personal, customizable, and interactive by using technologies such as interactive multimedia, digital comics, Augmented Reality, Virtual Reality, and automated assessment systems. Furthermore, AI also helps teachers manage learning more efficiently. Therefore, AI-assisted interactive learning media has proven effective as a learning innovation that can help improve digital literacy in elementary school students and align with the educational needs of the digital age.